Prenatal Cytogenetic Findings in 13.466 Cases of High-Risk Pregnant Women in One Laboratory - Özer, Leyla; Ünsal, Evrim; Ayvaz, Özge; Şen, Aşkın; Baltacı, Volkan (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: This study was aimed to evaluate cytogenetic findings of high risk pregnancies according to indications. STUDY DESIGN: Between years 2001 and 2009, a large series of 13466 pregnant women with various high-risk factors were referred to our genetic laboratory for prenatal genetic diagnosis. 12.124 amniocentesis, 212 chorionic villus sampling (CVS), 173 percutaneous umbilical blood sampling (PUBS) samples and 809 fetal and placental tissue samples (from aborted or from stillbirth fetuses) were collected. All of the cytogenetic findings were assessed retrospectively. We compared the cytogenetic results in the distribution of indication groups. RESULTS: Among all indications advanced maternal age was the most common indication. Chromosomal abnormalities were observed in 1029/13406 cases (7.6%). Trisomy 21 was the most common chromosomal abnormality found in 228/1029 cases (22.2%). Of sex chromosomal abnormalities, monosomies were the most common abnormality (3.3%). Of structural rearrangements translocations were the most common abnormality (2.3%). Balanced chromosome rearrangement carriers had the highest percentage of pregnancies with abnormal chromosomes. CONCLUSION: This study presents the largest series of cytogenetic findings on prenatal samples performed in Turkey. Analysis of samples of high risk pregnancies could provide an important database for prenatal genetic counseling and obstetric management for each indication groups.